Adsorptive removal of Pb (II) using exfoliated graphite adsorbent:influence of experimental conditions and magnetic CoFe2O4 decoration - Nguyen, Thi Thuong; Nguyen, Thi Ngoc Thu; Bach, Long Giang; Nguyen, Duy Trinh; Bui, Thi Phuong Quynh (IIUM Engineering Journal, 2019)
The worm-like exfoliated graphite (EG) based adsorbents prepared from low-cost natural graphite flakes via facile synthesis processes have been found to be efficient adsorbents when it comes to removing Pb (II) from aqueous solution. EG was fabricated by chemical intercalation and microwave assisted exfoliation. Furthermore, the magnetic exfoliated graphite (MEG) was developed by incorporating CoFe2O4 particles into the EG layers using the citric acid based sol-gel technique. Adsorption behaviour of Pb (II) on the as-prepared adsorbents was investigated by taking several experimental conditions into consideration such as contact time, initial concentration, adsorbent dosage, and pH value. The results with initial neutral pH indicated that the adsorption isotherms for Pb (II) on the EG and MEG were well consistent with the Langmuir isotherm model revealing the maximum adsorption capacity of 106 mg/g and 68 mg/g for EG and MEG, respectively. The adsorption kinetics of Pb (II) was found to adhere to the pseudo-second-order kinetic model. The chemical interaction between ? electrons on graphite sheets and Pb (II) ions was suggested to play an essential role in the adsorption mechanism. The introduction of magnetic CoFe2O4 to the EG was found to induce the shift of optimal pH value to a more basic condition. The characterization of the adsorbents was performed using relevant analysis techniques such as Scanning electron microscope (SEM), X–ray powder diffraction (XRD), vibrating-sample magnetometer (VSM), and Fourier-transform infrared (FTIR). The results of this work suggest a high possibility for application of the as-prepared modified graphite to remove hazardous substances in practical wastewater treatment systems. ABSTRAK: Penyerap Pengelupas Grafit (EG) yang berupa seperti cacing dihasilkan dari grafit semulajadi yang murah melalui proses sintesis serpihan, ia juga merupakan penyerap yang bagus dalam mengasingkan Pb (II) daripada larutan akues. EG direka dengan tindak balas interkalasi kimia dan pengelupasan melalui gelombang mikro. Tambahan, pengelupas grafit magnet (MEG) telah dihasilkan dengan memasukkan zarah CoFe2O4 ke dalam lapisan EG menggunakan teknik sol-gel yang berasaskan asid sitrik. Tindak balas penyerapan Pb (II) pada penyerap yang disiapkan ini, dikaji dengan mengambil kira beberapa keadaan eksperimen seperti waktu disentuh, konsentrasi awal, dos penyerap dan nilai pH. Hasil keputusan pH neutral awal menunjukkan bahawa isoterm penyerapan bagi Pb (II) pada EG dan MEG adalah konsisten dengan model isoterm Langmuir. Ini menunjukkan kapasiti penyerapan maksimum 106 mg/g dan 68 mg/g bagi EG dan MEG, masing-masing. Penyerapan kinetik Pb (II) didapati mematuhi model kinetik pesudo-order-kedua. Interaksi kimia antara elektron ? pada helaian grafit dan ion Pb (II) memainkan peranan penting dalam mekanisme penyerapan. Pengenalan magnet CoFe2O4 kepada EG didapati telah mengubah nilai pH optimum kepada keadaan asal. Pengelasan penyerapan dilakukan menggunakan teknik analisis yang relevan seperti Mikroskop Elektron Pengimbasan (SEM), Difraksi Serbuk sinar-X (XRD), Magnetometer Sampel-Getaran (VSM) dan Inframerah Perubahan-Fourier (FTIR). Hasil kerja ini mencadangkan kemungkinan besar bagi penggunaan grafit ubah suai yang disediakan bagi membuang bahan berbahaya dalam sistem rawatan air sisa praktikal.